Induced pluripotent stem cells for cardiovascular therapeutics: Progress and perspectives - Kizub, I. V. (Regulatory Mechanisms in Biosystems, 2023)
The discovery of methods for reprogramming adult somatic cells into induced pluripotent stem cells (iPSCs) opens up prospects of developing personalized cell-based therapy options for a variety of human diseases as well as disease modeling and new drug discovery. Like embryonic stem cells, iPSCs can give rise to various cell types of the human body and are amenable to genetic correction. This allows usage of iPSCs in the development of modern therapies for many virtually incurable human diseases. The review summarizes progress in iPSC research in the context of application in the cardiovascular field including modeling cardiovascular disease, drug study, tissue engineering, and perspectives for personalized cardiovascular medicine.